2003
DOI: 10.1159/000074425
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA 125 Levels in Patients with Chronic Heart Failure and Accompanying Pleural Fluid

Abstract: Malignant and nonmalignant serosal fluids have been found to be associated with high serum levels of CA 125, suggesting that the presence of fluid in the serosal cavities may stimulate its release. In this study, we investigated the relationship between serum CA 125 levels and the presence of pleural fluid in patients with chronic heart failure (CHF). We performed a clinical study in 36 patients with CHF with and without pleural fluid. Patients with CHF were divided into two groups based on the presence of flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
3
36
0
3
Order By: Relevance
“…It has become increasingly clear that mechanical stress and inflammatory stimuli together initiate CA-125 synthesis [34]. In the course of HF, CA-125 is positively correlated with the NYHA functional class, the presence of pleural effusion, and pulmonary capillary wedge pressure [35,36]. Nunez et al [37] found significant differences in CA-125 levels in patients with and without HF; patients with acute HF exhibited a 7-fold increase in mean CA-125 serum levels in comparison with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly clear that mechanical stress and inflammatory stimuli together initiate CA-125 synthesis [34]. In the course of HF, CA-125 is positively correlated with the NYHA functional class, the presence of pleural effusion, and pulmonary capillary wedge pressure [35,36]. Nunez et al [37] found significant differences in CA-125 levels in patients with and without HF; patients with acute HF exhibited a 7-fold increase in mean CA-125 serum levels in comparison with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Increased CA125 concentration in patients with HF is believed to be multifactorial and secondary to the increased end-diastolic and pulmonary venocapillary pressure that causes interstitial pulmonary edema [31] , an inflammatory substrate present in HF. In addition, the appearance of pleural effusion and signs of congestion have been associated with increased CA125 [32] . The good correlation of CA125 with natriuretic peptides suggests a similar release mechanism related to an increase in intracavitary pressures and stress of both atrial and ventricular walls.…”
Section: Ca125 and Hfmentioning
confidence: 99%
“…According to our results, there was a significant correlation between CA 125 serum levels and HF, including the correlation between this tumoral marker and BNP values. Many reports 12,14,19,36,37 have suggested that serosal fluids occurring in patients with HF are directly responsible for elevated serum CA 125 levels and that the presence of serosal fluid may stimulate the release of CA 125 rather than its cytopathological content. Recent studies have suggested that CHF may, in part, be an inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%